2020
DOI: 10.1093/asj/sjaa198
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study Assessing the Effect of Local Infiltration of Tranexamic Acid on Facelift Bleeding

Abstract: Abstract Background Rebound bleeding during facelift surgery is a major cause of facelift hematomas. Subcutaneous infiltration of tranexamic acid combined with lidocaine and epinephrine was recently retrospectively shown to decrease rebound bleeding. No study has prospectively examined the effect of subcutaneous TXA on intraoperative and postoperative bleeding during facelift surgery. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 45 publications
1
44
0
1
Order By: Relevance
“…Recently, the same group 28 conducted a prospective study to demonstrate that TXA with local anesthesia safely reduced the effects of rebound bleeding and postoperative drainage, and they reached similar conclusions.…”
Section: Face Liftmentioning
confidence: 73%
See 1 more Smart Citation
“…Recently, the same group 28 conducted a prospective study to demonstrate that TXA with local anesthesia safely reduced the effects of rebound bleeding and postoperative drainage, and they reached similar conclusions.…”
Section: Face Liftmentioning
confidence: 73%
“…One case series, 25 2 retrospective cohort studies, 26 , 27 1 prospective cohort, 28 and 1 RCT29 were identified regarding the use of TXA in facelift procedures involving 194 patients with an average age of 61.8 years. Of these patients, 94 underwent an extended deep plane facelift, 61 had a face lift with SMAS plication.…”
Section: Face Liftmentioning
confidence: 99%
“…Recent studies have suggested that tranexamic acid (TXA) may be beneficial in reducing facelift bleeding intraoperatively and decreasing surgical time by inhibiting fibrinolysis and clot dissolution. 15 , 16 However, evidence that it reduces hematoma rate is currently sparse. The ideal route—intravenous, topical, or subcutaneous infiltration combined with local anesthetic—remains unclear.…”
Section: Common Complicationsmentioning
confidence: 99%
“…The existing literature is lacking. Two prospective cohort studies (level II), 4,5 one retrospective cohort study (level III), 3 and two case series (level IV) 1,2 were evaluated.…”
Section: Level Of Evidencementioning
confidence: 99%
“…Recently the use of preoperative antifibrinolytic agents in various facial plastic and reconstructive surgeries has been described, but their use in rhytidectomy remains a topic of ongoing discussion. tranexamic acid (TXA) is an antifibrinolytic agent that inhibits clot breakdown and is well described in the literature to reduce intraoperative blood loss in craniofacial, cardiac, trauma, dermatologic, and orthopedic surgeries 2–5 . Despite the potential for TXA to decrease intraoperative blood loss in facelift, no formal guidelines exist for this use.…”
Section: Introductionmentioning
confidence: 99%